The Northern Ireland Research Initiative: Data on the Troubles from 1968 to 19981. (February 2014) - Loyle, Cyanne E.; Sullivan, Christopher; Davenport, Christian
In recent years the study of conflict has increasingly focused on the analysis of violence at the subnational level. Despite many advances, these efforts have been unable to address key questions within the literature, including inquires concerning the dynamic interactions between governments and challengers—the conflict–repression nexus. In this article, we present a new data project, the Northern Ireland Research Initiative or NIRI, and identify the ways in which this effort is particularly well suited to advance our understanding of the relationship between repression and dissent in Northern Ireland and beyond. NIRI is a disaggregated events-based dataset relying on new sources of conflict data that includes a broad range of actions (e.g. localized, short-term events and aggregate/larger-scale long-term activities) over the period of the Troubles in Northern Ireland (1968–1998).